2007
DOI: 10.1111/j.1365-3164.2007.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical tripeptide copper complex and helium‐neon laser on wound healing in rabbits

Abstract: The aim of this study was to compare the clinical and histopathological effects of tripeptide copper complex (TCC) and two different doses of laser application (helium-neon laser, 1 and 3 J cm(-2)) on wound healing with untreated control wounds. Experimental wounds were created on a total of 24 New Zealand white rabbits and topical TCC or laser was applied for 28 days. The wounds were observed daily, and planimetry was performed on days 7, 14, 21 and 28 to measure the unhealed wound area and percentage of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…TCC is a naturally occurring peptide-copper complex that has been shown to possess potentially interesting properties in the wound healing process in animal [21,37] and human models [20,38] . Observation of a positive effect by TCC on wound healing in the current study is consistent with other studies [23,24] which reported that Iamin, a TCC containing hydrogel, accelerates wound healing and wound contraction, and promotes epithelialization by creating a moist wound environment. The use of a hydrogel helps to produce more rapid healing by creating a moist environment which has superior features over a dry wound, such as prevention of tissue dehydration and cell death, accelerated angiogenesis, increased breakdown of dead tissue and fibrin, and potentiation of the interaction of growth factors with their target cells [39] .…”
Section: Gül Satar Cangül Topalsupporting
confidence: 93%
See 2 more Smart Citations
“…TCC is a naturally occurring peptide-copper complex that has been shown to possess potentially interesting properties in the wound healing process in animal [21,37] and human models [20,38] . Observation of a positive effect by TCC on wound healing in the current study is consistent with other studies [23,24] which reported that Iamin, a TCC containing hydrogel, accelerates wound healing and wound contraction, and promotes epithelialization by creating a moist wound environment. The use of a hydrogel helps to produce more rapid healing by creating a moist environment which has superior features over a dry wound, such as prevention of tissue dehydration and cell death, accelerated angiogenesis, increased breakdown of dead tissue and fibrin, and potentiation of the interaction of growth factors with their target cells [39] .…”
Section: Gül Satar Cangül Topalsupporting
confidence: 93%
“…Five-micrometer sections were stained with hematoxylin and eosin (H&E). Progressive decrease in neutrophil number and progressive increase in angiogenesis were selected for monitoring the healing process histopathologically as reported in previous studies [23,24] . In every skin section, an area just beneath the epidermis or crust formation was randomly selected.…”
Section: Histopathological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The measuring area was obtained comparing the amount of pixels inside perimeter and inside the known area using the mathematic expression: W a = (K a × N w )/N k , where W a = wound area, K a = known area, N w = number of pixels inside wound area and N k = number of pixels inside known area. Thus, the unhealed wound area and the percentage of wound contraction were calculated (Gul et al, 2008) and used for statistical analysis.…”
Section: Planimetrymentioning
confidence: 99%
“…LLLT is a widely studied treatment option for several different types of acute and chronic medical problems, and has been studied mostly in different types of animals until now. Some of the studies using animals as the target subjects have found some correlation between the use of LLLT and decreased healing times of wounds when compared to the control groups 6,7 . As more evidence of the statistically proven benefits of LLLT in animal trials have surfaced, some researchers have begun to shift their view to whether this treatment may have any beneficial properties in human wound healing.…”
Section: Resultsmentioning
confidence: 97%